Challenging the Need for Transparency, Controllability, and Consistency in Usable Adaptation Design - Kniewel, Romy; Evers, Christoph; Schmidt, Ludger; Geihs, Kurt (Electronic Communications of the EASST, 2013)
Adaptive applications constitute the basis for many ubiquitous computing scenarios as they can dynamically adapt to changing contexts. The usability design principles transparency, controllability, and consistency have been recommended for the design of adaptive interfaces. However, designing self-adaptive applications that may act completely autonomous is still a challenging task because there is no set of usability design guidelines. Applying the three principles in the design of the five different adaptations of the mobile adaptive application Meet-U revealed as difficult. Based on an analysis of the design problem space, we elaborate an approach for the design of usable adaptations. Our approach is based on a notification design concept which calculates the attention costs and utility benefits of notified adaptations by varying the design aspects transparency and controllability. We present several designs for the adaptations of Meet‑U. The results of a user study shows that the notification design approach is beneficial for the design of adaptations. Varying transparency and controllability is necessary to adjust an adaptation’s design to the particular context of use. This leads to a partially inconsistent design for adaptations within an application.